ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION WITH HAMSTRING AUTOGRAFT USING BIOABSORBABLE VERSUS TITANIUM INTERFERENCE SCREW IN TIBIAL TUNNEL IN GOVERNMENT HOSPITAL OF WEST NEPAL - Khadka , Tirthendra; Thapa , Prakash Bahadur; Kayastha , Nirab; Mishra , Rahul (Journal of Chitwan Medical College, 2022)
Background: Arthroscopic anterior cruciate ligament reconstruction can be performed both with titanium and bioabsorbable interference screws. The purpose of this study was to compare functional outcomes after reconstruction using these different implants. Methods: This was a retrospective study. Patients who underwent ACL reconstruction with hamstring autograft at Bheri hospital over the designed period were observed. Each group (titanium and bioabsorbable screws) consisting of 20 patients were compared using Lyshlom knee scores at 3, 6 and 12 months postoperatively. Statistical analysis was done using SPSS version 24. Chi square test was applied for comparing functional outcomes. Confidence interval of 95%, p value less than 0.05 was taken as significant. Results: Mean Lyshlom scores at 3, 6 and 12 months were 61.70, 69.60 & 85.90 for titanium group and 62.65, 70.95 & 84.65 for bioabsorbable screw group. The differences were not statistically significant. Conclusions: Functional outcomes at each follow up was equivalent among patients using either titanium or bioabsorbable screws.